Empowering civil society in the industrial revolution 4.0 : proceedings of the 1st International Conference on Citizenship Education and Democratic Issues (ICCEDI 2020), Malang, Indonesia, October 14, 2020 /: proceedings of the 1st International Conference on Citizenship Education and Democratic Issues (ICCEDI 2020), Malang, Indonesia, October 14, 2020. (2021) - Unknown
No abstract available